Goals! : how to get everything you want, faster than you ever thought possible - Tracy, Brian (BK life book., 2010)
Based on more than 20 years of experience and 40 years of research, this book presents a completely updated and practical, proven strategy for creating and meeting goals that has been used by more than 1 million people already in its first edition. Author Brian Tracy again explores the seven key elements of goal setting and the 12 steps necessary to set and accomplish goals of any size. Using his trademark simple language and real-life examples, Tracy shows how to do the crucial work of determining one's strengths, values, and true goals. He explains further how to build the self-esteem and confidence necessary for achievement; how to overpower every problem or obstacle; how to overcome difficulties; how to respond to challenges; and how to continue moving forward no matter what happens. The book's revised and updated "Mental Fitness" program of character development shows readers how to become the kind of person on the inside who can achieve any goal on the outside.